Chinese Stroke Association guidelines for clinical management of cerebrovascular disorders: executive summary and 2019 update of clinical management of stroke rehabilitation. Issue 3 (28th June 2020) - Zhang, Tong; Zhao, Jun; Li, Xueping; Bai, Yulong; Wang, Baojun; Qu, Yun; Li, Bingjie; Zhao, Shengjie
Abstract : Stroke is the third leading cause of long-term disability. Effective stroke rehabilitation should be provided to patients with a moderate or severe stroke so as to achieve functional recovery. Also, stroke rehabilitation is moving towards more intense therapy models that incorporate technologies such as robotics and computer games. Evidence-based guidelines are useful for promoting the best possible clinical practices. This guideline summarises the modes of stroke rehabilitation in China—three-stage rehabilitation network, rehabilitation of stroke dysfunction, training for activities of daily living, stroke complications and rehabilitation care. The aim of this guideline was to provide a synopsis of best clinical practices in the stroke rehabilitation of adult patients in China.